The Use of Webtoon Media to Improve Reading Comprehension of Eighth-Grade Students at SMPN Unggul Tunas Nusa - Irda Nadilla; Meristika Moetia (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study assessed Webtoon's efficacy as a digital teaching tool for raising eighth-grade students' reading comprehension at SMPN Unggul Tunas Nusa. Using a quasi-experimental research design with a pre-test and post-test, a quantitative research approach was used within a single group. Thirty‑five eighth‑grade students were purposively sampled as participants. The study was conducted across six meetings, comprising a pre‑test, four treatment sessions that used Webtoon based narrative texts, and a post‑test. The performance of the students was evaluated using a 20-item reading comprehension test with multiple choices both before and after the educational intervention. A Shapiro–Wilk normality test and a Wilcoxon signed-rank test were used to analyse the collected data because the data were not normally distributed. The findings demonstrated a considerable reading comprehension improvement following the use of Webtoon, with an average score rising significantly from 76.00 to 96.86 between the pre-test and post-test. Furthermore, The Wilcoxon Signed-Rank Test analysis yielded statistically significant results differences between the two sets of scores (Z = –5.212, p < 0.05). The effect size calculation (r = 0.881) also reflected a strong practical effect. Overall, the findings supported the effectiveness using Webtoon as an online teaching resource designed to enhance pupils' reading comprehension and suggested its integration into English language teaching to facilitate more interactive and engaging reading instruction.